CARBON CYCLES, NITROGEN FIXATION AND THE LEGUME-RHIZOBIA SYMBIOSIS AS SOIL CONTAMINANT BIOTEST SYSTEM - Werner, Dietrich (Indonesian Journal of Forestry Research, 2008)
The major pools and turnover  rates of the global carbon (C) cycles are presented and compared to the human production of CO2  from the burning of fossil fuels (e.g. coal and oil) and geothermal  fuels (natural  gases), both categorized as non-renewable energy resources which  in amount  reaches around  6.5 Gigatons C per year. These pools that serve as C-holding stallions  are in the atmosphere,  the land plant biomass, the organic soils carbon, the ocean carbon and the lithosphere. In another related case, the present focus in the area of nitrogen  fixation  is discussed with  data on world  production of grain  legumes  compared  to cereals production and nitrogen  fertilizer use. The focus to understand  the molecular  biology of the legume-rhizobia symbiosis as a major contributor to nitrogen  fixation  is in the areas of signal exchange between  host plants and rhizobia  in the rhizophere including  the nod factor signalling, the infection  and nodule compartmentation and the soils stress factors affecting the symbiosis. The use of the Legume-Rhizobia symbiosis as a biotest system for soil contaminants includes data for cadmium,  arsenate, atrazine,  lindane,  fluoranthene, phenantrene and acenaphthene and also results  on the mechanism,  why the symbiotic system is more sensitive  than test systems with plant growth  parameters.